Conscience without Cognition: The Effects of Subconscious Priming on Ethical Behavior - Welsh, David T.; Ordóñez, Lisa D. (Academy of Management Journal, 2014)
Research in the field of behavioral ethics has traditionally viewed ethical decision making as rational and deliberate. However, some recent research has proposed a dual process model of ethical decision making that has both conscious and subconscious components (Reynolds, 2006). We extend current theory by using subconscious ethical and unethical priming to test the effects of subconscious processes on ethical behavior through an automatic process of schema activation and implicit association. Studies 1 and 2 extend self-concept maintenance theory (Mazar, Amir, & Ariely, 2008) by exploring the mediated process through which subconscious ethical and unethical primes trigger the activation of moral standards, thereby influencing categorization and subsequent responses to morally ambiguous situations. Study 3 demonstrates that both subconscious ethical and unethical priming reduce dishonesty even when participants are unmonitored and are given difficult performance goals that previously have been shown to lead to unethical behavior.